Modelling the Predictors and Outcomes of Supply Chained of Brand Experience: Evidence from the Chained Fast Food Brand - Mohamed, Rozita Hj Naina; Bakar, Norzehan Abu; Rahman, Mohd Khirzan Badzli A.; Shahid, Siti Asiah Md.; Borhan, Halimahton (ExcelingTech, 2020)
Brand Experience can be the most privileged tool for differentiation in today’s highly competitive marketplace. Customer’s feeling, emotion and interactions will contribute to the overall perception of the brand experience. Undoubtedly, it is critical to gain insights into the key drivers of brand experience and subsequently ascertain its outcomes in order to design effective marketing strategies for market growth and perhaps business sustainability. The principal aim was to develop an integrative novelty model of brand experience and examine the predictors and outcomes of brand experiences of fast food brand share in Malaysia. The study applies SOR Model (Mehrabian-Russell, 1974), and other related branding models to a sample of 450 adult respondents who reside in chosen urban areas in Malaysia. The study has used a survey approach with self-administered questionnaire distributed in restaurants, offices and homes. Structural equation modelling was utilized to test the hypothesized relationships among the constructs, as postulated in the model. The measure employed in this study were rigorously assessed and purified initially via item analysis and exploratory factor analysis and subsequently refined by confirmatory factor analysis. It is reasonable to claim that they have adequately met the unidimensionality, validity and reliability criteria applied. Nine of the hypothesized links were supported and three rejected. Result of hypothesis model acceptable fit was CMIN/DF=3.45, RMSEA=0.074, GFI=0.931, CFI=0.958 and IFI=0.959. Ultimately, the study’s primary goal of developing an integrative model that has statistical and explanatory power, which could permit interpretation of results confidently, was achieved. Hence, the current investigation unequivocally illuminates several key contributions to the marketing theory, chained fast food industry practitioners and government bodies. Firstly, it exemplifies that ‘Product Quality’ is the key driver of the predictors of brand experience. Secondly, service quality and store image are not significant predictors of customers’ brand experience with the chained fast food brand. Thirdly, the findings suggest that brand experience is not significant predictor of customer’s commitment towards chained fast food brand. Finally, the current investigation confirms that trust was the most influential predictor on resonance and commitment is also revealed to be a significant predictor of resonance, but of a smaller magnitude compared to trust. Discussions of the results are provided along with contributions for the fast food industry and government and suggestions for future research.